Traumatic brain injury and abuse among female offenders compared to non-incarcerated controls. (6th December 2018) - O'Rourke, Conall; Linden, Mark A.; Lohan, Maria
ABSTRACT: Objective : To examine the prevalence of traumatic brain injury (TBI) and past abuse experienced by adult female offenders. Methods : Twenty-nine female offenders from a UK women's prison and twenty-nine age and gender matched university controls were recruited. In addition to demographic data, the Brain Injury Screening Index was utilized alongside the Childhood Trauma Questionnaire and the Abusive Behaviour Inventory. Results : Approximately 79% ( n = 21) of female offenders reported a history of TBI, with 38% ( n = 8) reporting six or more injuries. However, only 28.5% of female offenders reporting injury ( n = 6) believed they had sustained a brain injury. Prevalence of both childhood ( n = 15, 51.7%), and partner ( n = 19, 65.5%) abuse was also high among offenders. TBI Index scores correlated with past childhood and past partner physical abuse. Past mental illness, partner physical abuse, and number of convictions were predictive of greater TBI severity. Conclusion : This is the first European study to examine combined TBI and abuse among an exclusively female offender population. It suggests that TBI is as prevalent among incarcerated females as it is among males. The unique presentation of female offenders must be acknowledged if effective rehabilitation programs are to be implemented.